TINJAUAN PEMANFAATAN SLUDGE CAKE PABRIK PULP KRAFT SEBAGAI ENERGI ALTERNATIF MELALUI PROSES GASIFIKASI - Syamsudin Syamsudin (JURNAL SELULOSA, 2015)
Kraft pulp mills generate large amounts of sludge cake with typical calorific value of 24 MJ/kg (dry and ash-free basis). Sludge cake could be utilized as an alternative energy through gasification to produce medium gaseous fuel. Sludge cake has a high moisture content and low dewaterability, probably due to biomass from the microbial growth in the wastewater treatment by activated sludge. These problems could be overcome by the addition of filtration aid utilizing biomass waste from pulp mill and dewatering processes by TAMD method. Drying was continued by utilizing hot flue gas from the boiler or lime kiln. Steam gasification of sludge cake by allothermal model could produce a gaseous fuel with a calorific value of 11 MJ/Nm3. Allothermal gasification model of two reactors was able for handling sludge cake with a moisture content of <55%, but produce gas with a high tar content.Gasification or combustion of sludge cake on this model should be performed at temperatures >1200°C to prevent slagging and fouling problem. In contrast, allothermal gasification model of three reactors could produce gas with a low tar content. Heat of gasification reaction might be supplied from thecombustion of volatile gas. Pyrolysis could be performed at temperatures <500oC to permit adequateheat supply for gasification and high char yield. Substitution of natural gas with producer gas need topay attention to the redesign of the combustion process associated with the lower heat of combustion.Keywords: sludge cake, dewatering, gasification, steam, CO2, medium gaseous fuelABSTRAK Pabrik pulp kraft menghasilkan sludge cake dalam jumlah besar dengan nilai kalor tipikal 20 MJ/kg (dasar kering dan bebas abu). Sludge cake dapat dimanfaatkan sebagai energi alternatif melalui gasifikasi untuk menghasilkan bahan bakar gas medium. Sludge cake memiliki kadar air tinggi dan dewaterability rendah, disebabkan adanya biomassa hasil pertumbuhan mikroba pengolahan air limbahsecara lumpur aktif. Kendala ini diatasi dengan penambahan media bantu  filtrasi memanfaatkan limbah biomassa pabrik pulp dan proses dewatering dengan metode TAMD. Pengeringan dilanjutkan dengan memanfaatkan gas panas dari boiler atau lime kiln. Proses gasifikasi-kukus allothermal terhadap sludge cake dapat menghasilkan gas bakar dengan nilai kalor 11 MJ/Nm3. Gasifikasi allothermal model dua reaktor mampu menangani sludge cake dengan kadar air <55%, namun menghasilkan gas dengan kadar tar yang tinggi. Gasifikasi atau pembakaran sludge cake pada model ini sebaiknya dilakukan pada suhu di bawah 1200oC untuk menghindari terjadinya slagging dan fouling. Sebaliknya, gasifikasi allothermal model tiga reaktor dapat menghasilkan gas dengan kadar tar rendah. Panas reaksi gasifikasi mungkin dapat dipenuhi dari pembakaran gas volatil hasil pirolisis. Pirolisis dapat dilakukan pada suhu <500ºC dengan mempertimbangkan kecukupan suplai panas gasifikasi dan yield arang tinggi. Penggantian gas bumi dengan gas produser perlu memperhatikan redesign proses pembakaran terkait dengan panas pembakaran yang lebih rendah.Kata kunci: sludge cake, dewatering, gasifikasi, kukus, CO2, bahan bakar gas kalor medium